May measurement month 2017 campaign screening results from Venezuela: an analysis of blood pressure, abdominal circumference and body mass index. / Campaña de Medición del mes de mayo-2017: un análisis de los resultados de la presión arterial, circunferencia abdominal e índice de masa corporal en Venezuela. - Hernández-Hernández, Rafael; Octavio-Seijas, José Andrés; López-Rivera, Jesús; Morr, Igor; Costantini-Olmos, Antonieta P.; Gúzman-Franolic, Mónica L.; Silva, Egle; Duín, Amanda; Marval, José; Méndez-Amaya, Nedina Coromoto; Ruíz-Lugo, José Félix; Vásquez, Dámaso; et al. (Investigación Clínica, 2020)
Abstract. The present study had the purpose of evaluating the proportion of subjects with hypertension, treatment, control rates, and the relationship between blood pressure (BP) with body mass index and abdominal circumference in a cross-sectional study, as part of a worldwide study designed by International Society of Hypertension, performed during May 2017. After the protocol´s approval by the local Ethical Committee, 64 sites were included from eight Venezuelan regions. A short questionnaire was completed for each participant, including knowledge of taking antihypertensive treatment, diabetes, previous myocardial infarction or stroke, alcohol intake, and smoking. BP was measured in the sitting position three times after resting for 5 minutes, one minute apart, using mainly oscillometric devices. Height, weight and abdominal circumference were measured. Data analyses were performed by the MMM central team. 21644 individuals were screened. After multiple imputations, 10584 individuals [48.9% (50.7% male; 47.7% female)] had hypertension. Of subjects not receiving antihypertensive medication, 1538 (12.2%) were hypertensives. Of hypertensive individuals receiving antihypertensive medication, 2974 (32.9%) had uncontrolled BP. 15.6% of our sample had obesity according to their body mass index; 43.8% of women and 20.7% of men had abdominal obesity. BP was positively correlated with BMI and abdominal circumference. In this largest BP screening carried out in Venezuela, 48.9% of the individuals had elevated BP and 12.2% did not know that they had hypertension, and in one third of those with hypertension on treatment, BP was not controlled. 15.6% had obesity by BMI, and 35.1% abdominal obesity. Screening such as the MMM17 can evaluate the association between hypertension and obesity and therefore may help to inform control programs.Resumen. Se realizó el presente estudio con el objetivo de evaluar la proporción de sujetos con hipertensión, tratamiento, tasas de control y la relación entre la presión arterial (PA) con el índice de masa corporal y la circunferencia abdominal en un estudio transversal, como parte de un estudio mundial diseñado por la Sociedad Internacional de Hipertensión, realizada durante mayo de 2017. Luego de la aprobación del protocolo por el Comité de Ética local, se incluyeron 64 sitios de ocho regiones venezolanas. Se completó un breve cuestionario para cada participante, que incluye el conocimiento de tomar tratamiento antihipertensivo, diabetes, infarto de miocardio o accidente cerebrovascular previo, consumo de alcohol y tabaquismo. La PA se midió en posición sentada tres veces después de descansar durante 5 minutos, con un minuto de diferencia, utilizando principalmente dispositivos oscilométricos. Se midieron la talla, el peso y la circunferencia abdominal. Los análisis de datos fueron realizados por el equipo central de MMM. Se evaluaron 21644 personas. Después de múltiples imputaciones, 10584 individuos [48,9% (50,7% hombres; 47,7% mujeres)] tenían hipertensión. De los sujetos que no recibieron medicación antihipertensiva, 1538 (12,2%) eran hipertensos. De las personas hipertensas que recibieron medicamentos antihipertensivos, 2974 (32,9%) tenían BP no controlada. El 15,6% de nuestra muestra tenía obesidad según su índice de masa corporal; el 43,8% de las mujeres y el 20,7% de los hombres tenían obesidad abdominal. La PA se correlacionó positivamente con el IMC y la circunferencia abdominal. En esta encuesta de detección de la PA más grande realizada en Venezuela, el 48,9% de los individuos tenían presión arterial elevada y el 12,2% desconocían tener hipertensión, y en un tercio de aquellos con hipertensión en tratamiento, la PA no estaba controlada. El 15,6% tenía obesidad por IMC y el 35,1% obesidad abdominal. Los exámenes de detección como el MMM17 pueden estimar la prevalencia de hipertensión y obesidad y pueden ayudar a evaluar los programas de control.